Theoretical And Pedagogical Foundations For TheDevelopment Of Teachers’ Competence In TheContext Of Modern Information Technologies - Ismoil Eshmamatov (Euro Asian Journal Publishing, 2026)
In the current digital era, the integration of modern information technologies (MIT) into education has become central to the professional development of teachers. This study explores the theoretical and pedagogical foundations necessary to enhance teacher competence in digital environments. It provides a critical analysis of educational innovations, digital literacy standards, and strategies for pedagogical transformation in light of global technological trends. Emphasis is placed on developing ICT-based competencies that enable educators to adapt to evolving teaching models. Drawing on a review of scientific literature and empirical findings, the article proposes a conceptual model for the continuous development of teachers' professional skills, with specific attention to Uzbekistan’s educational context. Findings underscore the importance of coherent policy-making, institutional infrastructure, and sustained professional support in achieving effective digital transformation in education.
Keywords: Teacher competence; digital pedagogy; information technology